Marriage by Force? Contestation over Consent and Coercion in Africa - Bunting, Annie; Lawrance, Benjamin N. (Ohio University Press, 2016)
With forced marriage, as with so many human rights issues, the sensationalized hides the mundane, and oversimplified popular discourses miss the range of experiences. In sub-Saharan Africa, the relationship between coercion and consent in marriage is a complex one that has changed over time and place, rendering impossible any single interpretation or explanation.The legal experts, anthropologists, historians, and development workers contributing to Marriage by Force? focus on the role that marriage plays in the mobilization of labor, the accumulation of wealth, and domination versus dependency. They also address the crucial slippage between marriages and other forms of gendered violence, bondage, slavery, and servile status.Only by examining variations in practices from a multitude of perspectives can we properly contextualize the problem and its consequences. And while early and forced marriages have been on the human rights agenda for decades, there is today an unprecedented level of international attention to the issue, thus making the coherent, multifaceted approach of Marriage by Force? even more necessary.